FRAGRANCES FROM HEAVEN: THE RELEVANCE OF SMELLING IN UNDERSTANDING THE EARLY HISTORY OF ISLAM - Muhammad Thalal (Islam Futura, 2020)
This paper explores the social life of smell in the early period of Islam. It is part of the efforts to awaken the historical awareness of the senses in the discipline of Islamic history and to contribute to the emerging field of sensory studies in which the senses are incorporated into our understanding of the past. The study applies the sensory history technique in investigating the context in which Muslim noses smelled in the past; in particular, their use of aromatic materials. The main question of the study is: how did fragrance function in religious practices, and the daily lives of early Muslim society? After analyzing the Quran and the hadith as the primary sources, the study finds that religious rituals and practices have encouraged the massive use of fragrance products such as musk, ambergris, camphor, and saffron. Fragrance became one of the most needed commodities in early Muslim markets. The status of fragrance also shifted from luxury goods afforded only by the aristocrat classes as simply necessity goods due to the increase in demand by ordinary Muslims. However, the use of fragrance is also gendered. The study finds discrimination and restriction for men and women in applying perfumes. The prohibition against women from wearing strong fragrance in public was for protection, because the Arabian tribal society in the seventh century associated women with lower status, and they were more frequently subjected to sexual harassment. This initial research of the smell of fragrance is expected to broaden our horizon of how early Muslim societies lived and what their world smelled like in the past.